High power test of the first C-band spherical pulse compressor prototype. (November 2019) - Li, Z. B.; Fang, W. C.; Gu, Q.; Tan, J. H.; Huang, X. X.; Zhao, Z. T.
Abstract: Recently, a new C-band (5712 MHz) compact spherical radio frequency (RF) pulse compressor was designed and tested for Shanghai Soft X-ray Free Electron Laser Facility (SXFEL). This pulse compressor utilizes one high Q0 spherical RF resonant cavity that works with two TE1, 1, 3 modes and a dual-mode polarized coupler. The peak power multiply factor is 6.1 and average power gain 3.8 in theory. During the high power test, a peak power multiply factor of 5.74 and average power gain of 3.77 was achieved. This paper presents the RF measurement of the C-band spherical pulse compressor and the high power test results.